Demolition waste cement fiber concrete / Wan Ahmad Izzat Wan Abdullah and Hasni Suryani Mat Hasan - Wan Abdullah, Wan Ahmad Izzat; Mat Hasan, Hasni Suryani (2023)
In Malaysia, the awareness of recycling products is still weak in the people’s mentality, especially in the construction industry. The wastage of the demolition process is usually dumped into the landfill when the demolition material doesn’t hold much value to be reused. This continuous effect will eventually fill the waste demolition site with demolition waste, particularly concrete materials. The consequence of this issue will be several problems with surrounding like pest problem, environmental damage, bad views and health issue to surrounding resident. This study aims to develop an innovation to reuse demolition waste into building material. The objective is to identify the current issue of demolition waste material, to propose an innovative idea of demolition waste cement fibre concrete and to suggest the marketability of demolition waste cement fibre concrete. The study will continue to find a way to use the demolition waste material and to transform it into useful material that can be used again in construction industries as main product or the substitute and the study will use several methods to obtain the objective for this study, such as desk study, experimenting and lab test. The data from the finding using the mentioned method will be recorded and assessed to fit the criteria of commercialization of the product in the future market. The future of this innovation can be developed more into better material use for environmental benefits that fits the criteria of industries revolution 4.0.